The impact of the variability of ionospheric phase refractive index on radio signals instability (2011)
The ionospheric phase refractive index is a complex function that determines the attenuation and the trajectory of radio signals through the ionosphere. This complex refractive index model has been obtained using the Maxwell's equations, the tensorial conductivity equation, electron collision models, and the geomagnetic field model. The model has been used to study and investigate the phase refractive index on radio wave propagation for high latitude, low latitude and equatorial regions of the global ionosphere, at 1400 h LT, during the periods of high solar activity (Rz = 104.5, year 1970), moderate solar activity (Rz = 68.9, year 1972) and low solar activity (Rz = 12.6, year 1976). Our results showed that ionospheric phase refractive index is not constant, less than unity, increases with increasing propagating radio frequencies and for a particular propagating radio frequency, it increases with decreasing solar activity